Empowering Tourism Village MSMEs through Product Innovation and Social Media Branding: A Community Service Program in Wisata Domba Rancabango - Hani Siti Hanifah; Wufron M.S.M. Wufron; Eliya Fatma Harahap (Universitas Garut, 2025)
Tourism villages offer strong opportunities for local economic development, yet many micro, small, and medium enterprises (MSMEs) face challenges in product innovation and digital branding. This community service program aimed to empower MSMEs in Wisata Domba Rancabango, Garut Regency, through product innovation and social media branding. Using a participatory approach, the program involved situational analysis, capacity-building workshops, hands-on mentoring, and evaluation. The results show improvements in MSMEs’ ability to develop tourism-oriented products, enhance basic packaging and branding, and utilize social media platforms for promotion. These outcomes strengthened product attractiveness, digital visibility, and entrepreneurial awareness. Despite limitations related to program duration and digital literacy, the program demonstrates that integrating product innovation and social media branding effectively supports the empowerment of tourism-based MSMEs and can be replicated in other tourism villages.